The characteristics of stylistic and moral proverbs in artistic prose - Chareri, Kalil; Amiri, Masoud (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
That our article intending to elucidate the art if an Arab proverb as a historical document and civilized reflect many of the features of Arab Life by focusing mainly on aspects of ideals in the Arab artstic prose and will by goingto read carefully these ideal and deepened and a cases to meanings lying behind olrazama of and benefit from the effort put in by all values of Arab Preachers and Critics in order to develop This art. Came search component of introduction. We talked then about proverbs and the basis for the most important methods and characteristics ofstylistic and moral then embarked on talking about proverbs in Arabic books that we have seen manifestation clear of this art maole after lighting cash reveal some of their faces persuasive and Altamaha.